2016
DOI: 10.1111/jbi.12900
|View full text |Cite
|
Sign up to set email alerts
|

Historical and contemporary correlates of snake biogeographical subregions in the Atlantic Forest hotspot

Abstract: Aim Snake faunal dissimilarity within tropical forests is not well characterized, nor are the factors underlying these patterns. Our aim was to disentangle the ecological and historical factors driving biogeographical subregions (BSR) for snakes.Location Brazilian Atlantic Forest (BAF). MethodsWe compiled 274 snake inventories to build a species-by-site matrix and used unconstrained ordination and clustering techniques to identify the number of snake BSR. We applied an interpolation method to map axes of compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 36 publications
2
53
3
Order By: Relevance
“…They also regarded the issue of how we delimit and map biogeographical regions as critical for continentalscale macroevolutionary and biogeographical studies, in face of the lack of consistency and precision in the way supposed phytogeographic regions are partitioned, categorized and mapped. Recent studies have shown complex internal structure of amphibian and snake species assemblages in the domain (Vasconcelos et al 2014, Moura et al 2017, and a broad plant biogeographical split into its northern and southern parts (Carnaval et al 2014, Zizka et al 2018. The Atlantic Forest is one of the main vegetation domains of the continent, originally covering more than 1 000 000 km 2 with lowland, montane, semi-deciduous and deciduous forests, and coastal heath vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…They also regarded the issue of how we delimit and map biogeographical regions as critical for continentalscale macroevolutionary and biogeographical studies, in face of the lack of consistency and precision in the way supposed phytogeographic regions are partitioned, categorized and mapped. Recent studies have shown complex internal structure of amphibian and snake species assemblages in the domain (Vasconcelos et al 2014, Moura et al 2017, and a broad plant biogeographical split into its northern and southern parts (Carnaval et al 2014, Zizka et al 2018. The Atlantic Forest is one of the main vegetation domains of the continent, originally covering more than 1 000 000 km 2 with lowland, montane, semi-deciduous and deciduous forests, and coastal heath vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…The 24 snake species recorded in this study correspond to approximately 11% of the 219 species known from the phytogeographical domain of the Atlantic Forest (Moura et al 2016). In general, the observed richness to the PESP is similar than that of other sites in the low-elevated Southeast Atlantic Forest (e.g., Marques and Sazima 2004, Centeno et al 2008, Pontes and Rocha 2008, Hartmann et al 2009a,b, São Pedro and Pires 2009, Moura et al 2012, Trevine et al 2014).…”
Section: Discussionmentioning
confidence: 85%
“…One might surmise that because seems to be cryptic and rare, it has not been found in these coastal areas. However, we doubt that the species occurs in São Paulo given the distance of São Paulo from the southernmost known records and the distinct biogeographical regionalization from the core distribution of the species ( Moura 2016). It is also noteworthy that some records of voucher specimens from western Espírito Santo and northeastern Minas Gerais were recovered in low probability areas.…”
Section: Specimensmentioning
confidence: 99%
“…The scarcity of available records across a wide timeframe, virtually unknown population trends, and the possibility of extinction in some historical localities (e.g., the single record from Minas Gerais state) lead us to think that should be assessed et al Moura (2016); these represent, respectively, the coastal or seasonal dry forests from northern Bahia to southern Rio de Janeiro states (in which the core distribution of the species is located), and the Serra do Mar Coastal, Bahia Coastal, and Interior Forests (3 records).…”
Section: Specimensmentioning
confidence: 99%